2001
DOI: 10.1038/sj.bmt.1703057
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for mobilisation of Ph-negative progenitor cells from patients with CML: impact of different mobilisation regimens

Abstract: Summary:Mobilised peripheral blood stem cells are widely used for autografting in patients with chronic myeloid leukaemia (CML) and it is generally thought that a high proportion of Ph-negative progenitor cells in the graft is desirable. We report here the results of 91 stem cell mobilisations performed with various chemotherapy regimens followed by G-CSF. We show that mobilisation of Ph-negative cells is possible after diagnosis as well as in advanced stages of the disease. The yield of Ph-negative cells is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The yield may be improved with temporary interruption of imatinib, a manoeuvre that was also successful in individuals who failed mobilisation with prior continuing imatinib/filgrastim. The efficacy of G-CSF mobilisation in the context of continuing imatinib appears suboptimal when compared with most reported series of PBSC harvests from other CML patients using various chemotherapy-GCSF regimens 30,31 or an interferon-G-CSF combination. 32 Our decision to continue imatinib therapy during the cytokine mobilisation in a first cohort of patients was based on the absence of reported clinical data to support temporary interruption, and a postulated benefit that leukaemic stem cells stimulated into cell cycle may be rendered more susceptible to cellular inhibition induced by the continuous presence of imatinib.…”
Section: Spotlightmentioning
confidence: 97%
“…The yield may be improved with temporary interruption of imatinib, a manoeuvre that was also successful in individuals who failed mobilisation with prior continuing imatinib/filgrastim. The efficacy of G-CSF mobilisation in the context of continuing imatinib appears suboptimal when compared with most reported series of PBSC harvests from other CML patients using various chemotherapy-GCSF regimens 30,31 or an interferon-G-CSF combination. 32 Our decision to continue imatinib therapy during the cytokine mobilisation in a first cohort of patients was based on the absence of reported clinical data to support temporary interruption, and a postulated benefit that leukaemic stem cells stimulated into cell cycle may be rendered more susceptible to cellular inhibition induced by the continuous presence of imatinib.…”
Section: Spotlightmentioning
confidence: 97%
“…The estimated probability of survival was 84% and 51% at 2 years and 4 years, respectively. The East German Study Group for Hematology‐Oncology published their experience with 91 stem cell mobilizations for autografting in patients with CML 26. Of the regimens used, they observed that, although the combination of idarubicin and Ara‐C for 3–5 days mobilized Ph negative cells in most patients, high‐dose Cy was remarkably less effective.…”
Section: Discussionmentioning
confidence: 99%
“…Patients received different treatments during the course of the disease, including α‐IFN, hydroxyurea, and/or other treatments, prior to mobilization chemotherapy. Fifty‐two of 53 patients received chemotherapy for mobilization: 33 patients received idarubicin, Ara‐C, and etoposide (ICE;12 idarubicin 6–8 mg/m 2 per day on days 1–5, Ara‐C 600–800mg/m 2 per day on days 1–5, and etoposide 150 mg/m 2 per day on days 1–3); 4 patients received mini‐ICE23 (ICE at similar doses but over 3 days); 10 patients received idarubicin and Ara‐C24 (idarubicin 10 mg/m 2 per day on days 1–2 and Ara‐C 600 mg/m 2 per day on days 1–5); 4 patients received high‐dose hydroxyurea25 (3.5 g/m 2 per day on days 1–7); and 1 patient received high‐dose cyclophosphamide (Cy) 26. In all patients, chemotherapy was followed by G‐CSF (5–10 μg/kg per day subcutaneously until the end of the harvest).…”
Section: Methodsmentioning
confidence: 99%